Reformulation of the Cultural Heritage Law for Climate Adaptation Based on Local Wisdom - Isharyanto, Isharyanto; Caesar Bimantya, Deva Mahendra (Jambe Law Journal, 2026)
Climate change increasingly threatens the physical survival of cultural heritage sites throughout Indonesia, yet Law concerning Cultural Heritage remains silent on climate adaptation. This study examines the structural shortcomings of the statute and formulates directions for its reformulation through the incorporation of local wisdom. Employing doctrinal legal research, the study identifies three principal legal problems: the absence of norms governing climate adaptation and disaster mitigation, ambiguity in conservation standards, and disharmony between state law and the customary law of Indigenous communities. The analysis adopts both statute and conceptual approaches grounded in three theoretical frameworks. Legal pluralism explains the coexistence of state, customary, and religious legal orders within a single social field. Intergenerational justice imposes an obligation on the present generation to preserve cultural heritage for future generations. Adaptive governance requires regulatory arrangements capable of responding to ecological change. The findings reveal that the statute’s definitional, institutional, managerial, and penal provisions generate systemic vulnerability to hydrometeorological disasters while marginalizing Indigenous custodianship. In contrast, local wisdom provides proven adaptation mechanisms through organic material technology, sacred spatial zoning, vernacular architecture, hereditary custodianship, and customary sanctions. The study offers a novel contribution by proposing three reforms: introducing a climate adaptation chapter, recognizing customary conservation institutions, and reconstructing the sanction system so that the Cultural Heritage Law functions as responsive law. It converts the statutory silence on climate adaptation into a diagnosis of horizontal legal disharmony, and it treats local wisdom as the operational content of adaptation through legal syncretism rather than as cultural background.